Activity, Learning and Teacher Training: A Study from the Perspective of Professional Didactics: Actividad, aprendizaje y formación docente: un estudio desde la perspectiva de la didáctica profesional (2022)
Introducion: This text proposes reflections on teacher training, by pointing out the process that makes up their learning and development. The objective of this work is to bring a discussion about the way in which teaching learning occurs in their field of work, under the contributions provided by Professional Didactics. Methodology: The methodology outlined here is based on qualitative research, of a bibliographic nature, using content analysis, in which we seek, from the contributions of some authors, to ratify the expressive relevance of activity, learning and professional training for the positive exercise of a teacher’s attributions in their professional performance. Results and discussion: From these studies, we bring a discussion that points the classroom as a work environment is a privileged locus with regard to the development of pragmatic knowledge, while it is configured as a collaborative environment, being conducive to the evolution of teaching professionalism in the exercise of their métier.